2009
DOI: 10.1111/j.1600-0501.2008.01644.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural study of tissues surrounding replanted teeth and dental implants

Abstract: Objectives: The aim of this study was to describe the ultrastructure of the dento-gingival border at replanted teeth and implants. Material and methods: Wistar rats (8 weeks old) were divided into groups for replantation and implantation experiments. In the former, the upper right first molars were extracted and then immediately replanted. In the latter, pure titanium implants were used. All tissues were fixed, demineralized and embedded in epoxy resin for ultrastructural observations. Results: One week after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…Authors reported that the orientation of the fibers differs in rough and smooth surfaces: smooth surfaces revealed an orientation of fibers parallel to the implant surface, while porous-coated surfaces promoted the formation of perpendicular fibers. The presence of these fibers has been confirmed in the study of Shioya et al (Shioya et al 2009). The overall tissue was described as "an inflammation free scar tissue".…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Authors reported that the orientation of the fibers differs in rough and smooth surfaces: smooth surfaces revealed an orientation of fibers parallel to the implant surface, while porous-coated surfaces promoted the formation of perpendicular fibers. The presence of these fibers has been confirmed in the study of Shioya et al (Shioya et al 2009). The overall tissue was described as "an inflammation free scar tissue".…”
Section: Discussionmentioning
confidence: 52%
“…In a work on rats (Ikeda et al 2000), the presence of a basal lamina and hemidesmosomes in peri-implant junctional epithelium was confirmed although it was stated that the finding of a basal lamina was less evident than on the control tooth sites, and it was well detectable only in the lower part of junctional epithelium. Results from a more recent article by Shioya et al (Shioya et al 2009) differ greatly by the work of Ikeda et al 2000. One week after implant insertion, peri-implant epithelium was observed and 8 weeks after implant insertion, the peri-implant epithelium receded, and the implant interface appeared to be sealed by aligned special cells with surrounding elongated fibroblasts and bundles of collagen fibers.…”
Section: Discussionmentioning
confidence: 82%
“…12. Electron micrograph of peri-implant epithelium at 8 weeks after implantation (CaTiO 3 implant) 3.5.2 Interface between dental implant and connective tissue Alternative structures of peri-implant tissues were reported (Abrahamsson et al, 2002;Berglundh et al, 2007;Moon et al, 1999;Shioya et al, 2009). A layer of aligned, epitheliallike cells emerged within peri-implant tissue, and this cell layer was unaccompanied by any structures related to attachment apparatus, including hemidesmosomes or basement membrane (Fig.…”
Section: Interface Between Dental Implant and Epitheliummentioning
confidence: 99%
“…However, if avulsed teeth are immediately replanted with minimum extra-oral dry time, "favorable healing" results, with repair of damaged root surface by cementum (Andreasen, 1981;Line et al, 1974). In a recent study, tissues around replanted teeth in rat were examined morphologically and ultrastructurally in detail in order to determine whether the attachment apparatus at the dentogingival border was regenerated following replantation (Shioya et al, 2009). Rat molars, luxated and extracted with care to keep damage to the surrounding tissues to a minimum, were immediately replanted into their original sockets.…”
Section: Dentogingival Border Of Replanted Toothmentioning
confidence: 99%
See 1 more Smart Citation